“Diritto di punire” o “Potere di morte”?: crimine, violenza e giustizia in “Mineirinho” di Clarice Lispector - Luigia De Crescenzo (Altre Modernità, 2016)
This essay analyses the concepts of crime and justice presented by Clarice Lispector in “Mineirinho”. This story was first published in June 1962 in the magazine Senhor with the title "Uma grama de radium-Mineirinho” and was later included in the section "Fundo de Gaveta” of the collection of stories A Legião Estrangeira (1964).